Profit comparisons, market prices and managers' judgments about negotiated transfer prices. - Luft, Joan L.; Libby, Robert (The Accounting Review, 1997)
This paper examines experienced managers' judgments about the effects of market price and accounting profit information on negotiated transfer prices. Conventional economic arguments predict that market price should determine negotiated transfer prices by determining reservation prices for parties with outside options. We found, however, that experienced managers expected the influence of market price to be limited by divisional managers' concern about how their profits compare with each other. While market price did affect managers' reservation-price and transfer-price estimates, its influence was significantly less when market price resulted in a more unequal ("unfair") distribution of profits between divisions. Profit comparisons also affected the judgments that determine the efficiency of the bargaining process. We found that as market price diverged from a price that offered equal profits to both divisions, both variance and bias in managers' price estimates increased, indicating that it would be harder to reach agreement on a transfer price.